2022
DOI: 10.1002/celc.202101648
|View full text |Cite
|
Sign up to set email alerts
|

MOF‐Derived Cu/Bi Bi‐metallic Catalyst to Enhance Selectivity Toward Formate for CO2 Electroreduction

Abstract: Converting CO2 into high‐value liquid products is a promising strategy to alleviate energy crisis. Herein, a novel Cu/Bi bi‐metal catalyst derived from MOFs has been prepared by a hydrothermal synthesis combining with high temperature calcination under N2 atmosphere, which shows cylindrical morphology composed of bi‐metallic nanoparticles. It is found that Cu/Bi bi‐metallic system is beneficial to lower the activate energy barrier of CO2 and shows a stronger adsorption capability for the CO2 ⋅ − intermediate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The above results consistently indicate the high selectivity for HCOOH formation on SU-101, which corresponds well with the experimental results. This can be explained by two aspects: on one hand, the easier adsorption of CO 2 than H makes the CO 2 RR a more advantageous reaction than the HER; 35,36 on the other hand, the adsorption of CO 2 on SU-101 is not strong enough to weaken the C]O bond and thus the CO generation is not favourable.…”
Section: And Tablementioning
confidence: 99%
“…The above results consistently indicate the high selectivity for HCOOH formation on SU-101, which corresponds well with the experimental results. This can be explained by two aspects: on one hand, the easier adsorption of CO 2 than H makes the CO 2 RR a more advantageous reaction than the HER; 35,36 on the other hand, the adsorption of CO 2 on SU-101 is not strong enough to weaken the C]O bond and thus the CO generation is not favourable.…”
Section: And Tablementioning
confidence: 99%
“…As shown in Figure 2c, the Bi 4 f XPS spectrum of Bi 2 O 3 and Ag−Bi 2 O 3 were all deconvoluted into two separate components centred at 164.3 and 158.9 eV, which are ascribed to the Bi 3+ 4f 5/2 and Bi 3+ 4f 7/2 states [10,20] . The first of the O 1s region spectra of Bi 2 O 3 and Ag−Bi 2 O 3 in Figure 2d comprise three components with BEs of 532.7, 531.2, and 529.5 eV, which correspond to the adsorbed water on the surface, Bi(OH) 3 and Bi−O lattice oxygen, respectively [12,21] . The Bi−O lattice oxygen had a significantly higher area in the case of the Ag−Bi 2 O 3 nanofibers, suggesting more oxygen defects in Ag−Bi 2 O 3 compared to Bi 2 O 3 , indicating that more oxygen was introduced to the matrix of Ag−Bi 2 O 3 and could result in more active sites.…”
Section: Resultsmentioning
confidence: 94%
“…The characteristic peaks at 450.43 and 441.98 eV are attributed to In 0 , indicating the presence of metal In. Compared with BiInO-0.43@C, the In 3d peak of BiInO-0.67@C shifted to higher binding energy (Figure c), illustrating that the valence state of In in BiInO-0.67@C was slightly higher. , In addition, the O 1s spectra are convolved into four peaks located at 534.13, 532.78, 531.78, and 530.08 eV, which can be assigned to the adsorbed oxygen species, In–O, OH (H 2 O), and Bi–O, respectively (Figure d) . It is found that both BiInO-0.67@C and BiInO-0.43@C have a certain amount of adsorbed oxygen, indicating that appropriate In doping is conducive to the generation of oxygen defects (Figure d).…”
Section: Resultsmentioning
confidence: 96%
“…51,52 In addition, the O 1s spectra are convolved into four peaks located at 534.13, 532.78, 531.78, and 530.08 eV, which can be assigned to the adsorbed oxygen species, In−O, OH (H 2 O), and Bi−O, respectively (Figure 2d). 53 It is found that both BiInO-0.67@C and BiInO-0.43@C have a certain amount of adsorbed oxygen, indicating that appropriate In doping is conducive to the generation of oxygen defects (Figure 2d). Additionally, XPS spectra of the single component materials (Bi 2 O 3 @C and In 2 O 3 @C) were tested for comparison with BiInO-0.67@C (Figure S10).…”
Section: Resultsmentioning
confidence: 97%